Co-producing the Gender and Climate Action Plan for Agriculture in Senegal: Process and lessons learnt - Segnon, Alcade Christel; Obossou, Abrewa Remilokoun Esdras; Diagne, Djibril; Dieye, Bounama; Zougmore, Robert Bellarmin (2025)
Developing countries, including Senegal, face persistent gender inequalities and policy barriers to advance Climate-Smart Agriculture (CSA). Despite its potential to improve food security and resilience, CSA remains constrained by structural inequalities, weak institutional coordination, and limited access to assets and climate information among women farmers. This InfoNote distils lessons learnt from the co-production process for developing the Gender and Climate Action Plan (GCAP) for Agriculture in Senegal, technically and financially supported by AICCRA. The evidence-based and participatory co-production process, engaging key stakeholders at local and national scales right from the design phase, was key to ensuring legitimacy, credibility, and policy relevance. Interdisciplinary collaboration, sustained engagement, and adaptive management improved the technical rigor and institutional coherence of the process, although challenges remain around resource mobilization for implementation. The Senegal experience demonstrates that co-producing gender-responsive CSA policies through inclusive, evidence-driven, and flexible processes can be a powerful model for other West African countries. Scaling up, however, requires institutional anchoring, continuous stakeholder engagement, and dedicated resources to translate policy frameworks into transformative action.